KSZE-Prozess und Perestroika in der Sowjetunion. Demokratisierung, Werteumbruch und Auflösung 1985-1991 - Saal, Yuliya von (Quellen und Darstellungen zur Zeitgeschichte, 2014)
The Soviet leadership was certain of its success after the signing of the Final Act of the CSCE (Conference on Security and Cooperation in Europe), and especially pleased with the agreements on trust-building measures. Yulia von Saal`s study convincingly shows how the Kremlin underestimated the explosive power of the Final Act in terms of civil and human rights, which launched it on a path of constantly mounting pressure for democratization.